“Od Chopina do … Noskowskiego”? Zygmunt Noskowskis langer Weg zu Chopin - Keym, Stefan (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2010)
The aim of this text is to present the process whereby Zygmunt Noskowski grew closer to the music of Chopin, which he initially treated with considerable distance. In the first part of the article, the author analyses verbal testimony of Noskowski’s Chopin reception on the basis of extant columns written by him. Noskowski’s attention first focused on Chopin towards the end of the 1880s, the catalyst being the Chopin anniversaries celebrated in 1894 and 1899, for the purposes of which Noskowski arranged piano compositions by Chopin for orchestra and voice. The picture of Chopin sketched by Noskowski in his press writings contained Classicist components in which his sense of form and his affinities with the work of Bach were underlined; on the other hand, Noskowski stressed in Chopin’s music – as a specifically Polish characteristic – its links with nature. Both these factors influenced the shape of Noskowski’s own music. In the second part of the article, the author shows Chopin’s influence on Noskowski’s compositions, which initially found expression through the intermediary of the dramatic aspects of the Second Symphony of Ignacy Feliks Dobrzyński, and then in episodic links between Noskowski’s symphonic poem Step [The steppe] and Chopin’s Rondo à la krakowiak, Op. 14. The climactic point of Noskowski’s dialogue with Chopin is defined by his programmatic-patriotic orchestral work Z życia… [narodu] [From the life… [of the nation]], in which Chopin’s Prelude in A major from opus 28 served as the basis for a set of variations; this work, despite a number of inconsistencies, is regarded by the author as an important work, both in its from and in its culturalhistorical significance.
Keywords: Fryderyk Chopin; Zygmunt Noskowski; reception; aesthetics; analysis; variation form; national music; programme music